The Influence of Visual and Audio Content on Conversational Implicature in English Listening: an Examination of Videos, Podcasts, and Transcripts - Rakhmatova Mekhriniso Musinovna; Azimjonova Elena Tulkunovna (Miasto Przyszłości, 2023)
Due to increasing digitalization in educational setting as well as in society, requirements and demands on schools, teachers, and pedagogical tools have changed. Some digital tools that have influenced the field of education are videos, podcasting and transcripts. This article examines the influence of visual and audio content on conversational implicature in English listening. Through the analysis of videos, podcasts, and transcripts, the study aims to understand how different forms of media impact the interpretation of implied meanings in conversational language. The research will explore how visual cues, such as body language and facial expressions, and audio cues, such as tone of voice and intonation, contribute to the understanding of conversational implicature. By examining various forms of media, the study seeks to provide insights into how different modes of communication influence the interpretation of implied meanings in conversational English.